Logistika v kmetijstvu - Lisec, Andrej (2022)
Logistics in Agriculture. The book deals with logistics in agriculture, which includes chapters on logistics related to agriculture, history in this field, food production, self-sufficiency in connection with the distribution of locally produced food, mechanization, transport of food in controlled temperature conditions, crop labeling, agricultural waste and a view of agriculture in the future, including the use of drones.
Keywords: logistics; agriculture; self-sufficiency; distribution of locally produced food; waste